The formal nature of law and the plurality of legal systems (Società e diritti, 2017)
A legal system needs that every society is organized by a complex of rules that emanates from its governing bodies. That rules must be categorical, as they don’t allow-unless anticipated cases -, to infringe them. Thereby thus gives rise to a structure that defines the way of being of the people and of the things in their mutual relationships, as an external and formal reality defined by the rules, that counterpose itself to the substance of the social relationships. The social datum cannot prevail on the rule without violating the principle of legality and every rule of civilness; as well as, even before, without letting the same existence of the legal system impossible to exist. As every society is endowed with a its own normative complex, the legal systems are numerous.Key words: Rule, Form, Society